THE EFFECT OF THE CONTEXTUAL TEACHING AND LEARNING (CTL) LEARNING MODEL ON THE OUTCOMES OF LEARNING SCIENCES IN THE STYLE MATERIAL OF GRADE IV OF STATE ELEMENTARY SCHOOL 6 RANTAU BAYUR - Anisa, Selfia Putri; Manullang, Jujur Gunawan; Lubis, Patricia H.M. (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2026)
This study aims to determine the effect of the Contextual Teaching and Learning (CTL) learning model on the learning outcomes of science on the material of force of class IV of SD Negeri 6 Rantau Bayur. The subjects of the study were 25 students of class IV of SDN 6 Rantau Bayur who would be treated using the Contextual Teaching and Learning (CTL) learning model in the subject of science, chapter III, material force, topic A, the effect of force on objects. The research method used was Quasi Experiment Non-Equivalent Control Group design, using two experimental and control classes, data collection techniques using observation and tests. Data analysis techniques used descriptive statistics and used normality tests, homogeneity tests, hypothesis tests, namely Independent Sample T Test. The results of the Pre-test calculation in the experimental class were 54.40% and the Post-test of the experimental class was 80.52% while the control class was 54.64% and the results of the Post-test value of the control class were 67.48% that there was an increase in the experimental class after the implementation of the Contextual Teaching and Learning (CTL) learning model. This is proven by the results of the hypothesis test which obtained a Sig. (2-tailed) value of 0.000 < 0.05, that HO is rejected and HA is accepted. Thus, there is a significant difference between the average learning outcomes of students in the subject of science and science.